The Impact of Capital Structure on Firm Performance with Growth Opportunity as the Moderating Variable: An Empirical Study on Manufacturing Firms Listed on IDX - Poerwono, Salvator B1024141002 (Jurnal Manajemen Update, 2017)
The importance of capital structure has drawn managers’ attention as it might determine the fate of a company. Companies capable of planning appropriate capital structure strategies are able to gain a competitive advantage in low cost and thereby enhancing the firm performance. Consequently, this study is aimed to analyze the impact of capital structure on firm performance of manufacturing firms listed on IDX moderated by growth opportunity.This study uses a sample of 94 manufacturing firms listed on IDX during 2012 - 2016 which makes up 470 total observations. The capital structure is measured by total debt to total assets ratio (TDTA) while the firm performance is measured by two proxies, namely profitability (ROA) and firm value (Tobin’s Q). In addition, a moderating variable growth opportunity (GROWTHOP) and four controlling variables firm size (SIZE), firm age (AGE), business risk (BUSRISK) and tangibility (TANG) are added. The data are analyzed using multiple regression analysis with ordinary least square (OLS) estimation.The finding indicates a mixed result, showing that capital structure affects profitability in negative direction, but affects firm value in positive direction. Another finding shows that growth opportunity can influence the relationship between capital structure and profitability, but not the capital structure-firm value relationship. However, growth opportunity does not strengthen the relationship between capital structure and firm performance proxied by either ROA or Tobin’s Q. The other finding shows that firm size has positive influence on firm performance. Besides, firm age is found to have negative relationship with only firm value while tangibility is proved to negatively affect profitability but not firm value. Lastly, the relationship between business risk and firm performance is not significant. Keywords: Capital Structure, Firm Performance, Profitability, Firm Value, Growth Opportunity